Do higher corporate taxes reduce wages? Micro evidence from Germany - Fuest, Clemens; Peichl, Andreas; Siegloch, Sebastian (Mannheim, 2016)
"This paper estimates the incidence of corporate taxes on wages using a 20-year panel of German municipalities. Administrative linked employer-employee data allows estimating heterogeneous worker and firm effects. We set up a general theoretical framework showing that corporate taxes can have a negative effect on wages in various labor market models. Using an event study design, we test the predictions of the theory. Our results indicate that workers bear about 40% of the total tax burden. Empirically, we confirm the importance of both labor market institutions and profit shifting possibilities for the incidence of corporate taxes on wages."